Design and development of stereo motion for mobile observation center - Muhammad Naufal, Mansor; Sazali, Yaacob; Nagarajan, R.; Hariharan, M. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.